Plant Science Structure, Anatomy and Physiology in Plants Cultured in Vivo and in Vitro - Gonzalez, Ana; Rodriguez, María; Gören Sağlam, Nihal (IntechOpen, 2020)
Over seven chapters, this book helps readers to integrate knowledge of plant anatomy, physiology, and morphogenesis as well as consider the conditions of the different environments to which plants are exposed. It highlights the importance of knowledge of the anatomy of plant tissues for different applications. In addition to the variety of physiological studies presented here, the book also emphasizes anatomical studies in botanical quality control of medicinal herbs with human health benefits. It is reflected in this book that studies on plant structure have greatly benefited from the new approaches and techniques available today.